The political machine : assembling sovereignty in the Bronze Age Caucasus - Smith, Adam T. (The Rostovtzeff lectures, 2017)
'The Political Machine' investigates the essential role that material culture plays in the practices and maintenance of political sovereignty. Through an archaeological exploration of the Bronze Age Caucasus, Adam Smith demonstrates that beyond assemblies of people, polities are just as importantly assemblages of thingsfrom ballots and bullets to crowns, regalia, and licenses